Mapping Pre-service Teachers' Experiences in Integrating Design Thinking and ChatGPT: An Analysis of 21st-Century Learning Tools Development. - Yuniawatika; Nusantara, Toto; Subanji; Anwar, Lathiful (Pertanika Journal of Social Sciences & Humanities, 2026)
Despite growing interest in Design Thinking and artificial intelligence (AI) in education, empirical research examining how pre-service teachers integrate these approaches into instructional design remains limited. Teacher training programs often lack structured guidance for such integration, creating a gap in preparing educators for 21st-century classrooms. Addressing this gap, this study explores the experiences of Pre-service Teacher Professional Education (PPG Prajabatan) students in Indonesia as they integrate the Design Thinking method with the AI tool ChatGPT to develop 21st-century learning tools. Employing a qualitative exploratory approach, the study utilised the Gioia method, selected for its systematic rigour in developing grounded theoretical insights through progressive abstraction from raw data to theoretical concepts. Data were collected through semi-structured interviews with 20 participants. The findings reveal three key conceptual contributions: (1) the pedagogical roles of ChatGPT as a cognitive support tool facilitating ideation, content generation, and iterative feedback; (2) a process model for Design Thinking-AI integration encompassing the empathise, define, ideate, prototype, and test phases; and (3) the emergence of reflective digital literacy as a critical competency for pre-service teachers. While Design Thinking enabled prospective teachers to gain a deep understanding of students' needs through diagnostic assessments, ChatGPT supported the formulation of learning objectives and the design of teaching materials. The study acknowledges limitations inherent to qualitative research, including the contextual specificity of findings to the Indonesian PPG program and the interpretive nature of thematic analysis. Ultimately, it contributes to the design of innovative and adaptive teacher training strategies for the digital age.